Hierarchical Inconsistency: A Monitoring Mechanism to Reduce Securities Fraud in Emerging Markets - Guo, Yidi; Luo, Xiaowei Rose; Li, Danyang (Organization Science, 2022)
Research has indicated limited effects of formal governance measures on securities fraud prevention in emerging markets due to the weak rule of law. We propose that hierarchical inconsistency, misaligned rank ordering in formal organizational and informal social hierarchies of the corporate elite, can provide a novel monitoring mechanism to reduce securities fraud. Leaders at the top of the two inconsistent hierarchies can feel distressed and motivated to engage in contestation and challenge each other’s authority, thus providing checks and balances and preventing groupthink. This monitoring effect is likely to be stronger when either of the two heads has dominant and unequivocal superiority in their respective hierarchy, making them particularly distressed by the hierarchical inconsistency and prone to contest. We test our argument in the context of publicly listed family-controlled firms in China, where business and family hierarchies may confer superiority to different individuals. Our study contributes to the corporate securities fraud literature by understanding how formal organizational structures and informal social relationships interact and jointly influence governance effectiveness in emerging markets. Funding: This work was supported by the Strategic Management Society [2015 SRF Dissertation Research Grant], Rudolf and Valeria Maag research funds, and INSEAD alumni funds.